The Construction of Historical Empathy in Learning History with a Global Diversity Perspective - Ilyasin, Ilyasin; Amin, Syaiful; Atmaja, Hamdan Tri (Indonesian Journal of History Education, 2022)
The purpose of the research was to find out the implementation of historical learning of the national movement, to find out the perceptions of Chinese students on historical learning of national movements and to find out the obstacles in historical learning of the national movement in Wonosobo Christian High School. The researchers used qualitative research methods. The data sources of this research are informants, documents and others data. The data collection techniques used observation, interviews, and documentation. The data analysis technique used is data analysis techniques with interactive models including data reduction, data presentation, inference, and verification. The implementation of historical learning on the subject of national movements carried out through the planning and implementation stages. In planning stage the teacher are prepares leasson plan, the media, learning methods in from of group discussions and learning material. The perception Chinese student of learning history of national movements are differing one another. This is caused by internal factors and external factors that influence their perception of historical learning, the subject of the national movement. In learning the history of the subject of the national movement, chinese students have their own obstacles. Regarding the status of Chinese ethnic students does not become a barrier to learning because high tolerance at the school.